The Non-peptide Angiotensin-(1–7) Mimic AVE 0991 Attenuates Delayed Neurocognitive Recovery After Laparotomy by Reducing Neuroinflammation and Restoring Blood-Brain Barrier Integrity in Aged Rats - Mi, Xinning; Cao, Yiyun; Li, Yue; Li, Yitong; Hong, Jingshu; He, Jindan; Liang, Yaoxian; Yang, Ning; Liu, Taotao; Han, Dengyang; Kuang, Chongshen; Han, Yongzheng; et al. (Frontiers in Aging Neuroscience, 2021)
Delayed neurocognitive recovery (dNCR) after surgery is a common postoperative complication in older adult patients. Our previous studies have demonstrated that cognitive impairment after surgery involves an increase in brain renin–angiotensin system (RAS) activity, including overactivation of the angiotensin 2/angiotensin receptor-1 (Ang II/AT1) axis, which provokes the disruption of the hippocampal blood–brain barrier (BBB). Nevertheless, the potential role of the counter-regulatory RAS axis, the Ang-(1–7)/Mas pathway, in dNCR remains unknown. Using an aged rat model of dNCR, we dynamically investigated the activity of both axes of the RAS following laparotomy. AVE 0991, a nonpeptide analogue of Ang-(1–7), was administered intranasally immediately after laparotomy. We found that the elevation of Ang II induced by surgery was accompanied by a decrease of Ang-(1–7) in the hippocampus, but not in the circulation. Surgery also significantly downregulated hippocampal Mas receptor expression at 24 h postsurgery. Mas activation with intranasal AVE 0991 treatment significantly improved hippocampus-dependent learning and memory deficits induced by surgery. Furthermore, it attenuated hippocampal neuroinflammation, as shown by the decreased level of the microglial activation marker cluster of differentiation 11b (CD11b) and the decreased production of several inflammatory molecules. Along with these beneficial effects, AVE 0991 treatment also alleviated the imbalance between matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of matrix metalloproteinase-3 (TIMP-3), and modulated the expression of occludin but not zonula occludens-1 (ZO-1), thereby restoring the ultrastructural integrity of the BBB. In conclusion, these data indicate that activation of Mas by AVE 0991 attenuates dNCR after surgery by reducing neuroinflammation and restoring BBB integrity. Our findings suggest that the Ang-(1–7)/Mas pathway may be a novel therapeutic target for treating dNCR after surgery in older adult patients.